Possibilities of internationalizing the penal policy in the field of criminalization - Radi, Nour; Al-Shammari, Kadhim (Journal of Legal Sciences, 2023)
The penal policy has an essential role in guiding the legislator to determine the interests worthy of penal protection. which are numerous and varied according to the circumstances and needs of each society, and that determining those interests within the community is closely related to the culture of that society and its political, economic and social systems, and given the diversity of societies in their culture and systems, so they vary -Generally- its penal policies accordingly. But this does not preclude the existence of common criminalization shared by all the legislations of the countries of the world. and which agree to criminalize all religions and human beliefs and international covenants, which pave the way for the possibility of developing and expanding the scope of the penal policy in the field of criminalization through the adoption of the internationalization system as a mechanism To develop and expand the scope of the penal policy. That is why we called the topic of the research the means of internationalizing the penal policy in the field of criminalization.